Pengaruh Product Quality dan Price Terhadap Loyalitas Pelanggan Dimediasi oleh Customer Satisfaction pada Pembelian Bolu Menara di Medan Selayang - Sari, Mayang; Suryani, Wan (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2025)
The purpose of this research is to determine and analyze the influence of product quality, price and customer satisfaction on purchase intention, to determine the influence of product quality and price on customer satisfaction, to determine and analyze the influence of product quality on customer loyalty mediated by customer satisfaction, and to determine and analyze Price has an effect on customer loyalty, mediated by customer satisfaction when purchasing Bolu Menara in Medan Selayang. The population in this study was the population of Medan Selayang sub-district, 103,559. The samples in the study were 85 taken using the Hair formula. The data collection technique used in this research was carried out by distributing questionnaires. The analysis technique in the research uses SmartPLS (Partial Least Square) starting from model measurement (outer model), model structure (inner model) and hypothesis testing. The results of the research show that product quality, price and customer satisfaction have a positive and significant effect on customer loyalty, product quality and price have a positive and significant effect on customer satisfaction, product quality has a positive and significant effect on customer loyalty mediated by customer satisfaction and price has a positive and significant effect on Customer loyalty is mediated by customer satisfaction when purchasing Bolu Menara in Medan Selayang.